Comparative Evaluation of Conventional and Advanced Magnetic Resonance Imaging (MRI) Sequences in Mesial Temporal Lobe Sclerosis Patients with Seizure - Vishakha Mittal; Rajul Rastogi; Vijai Pratap; Satish Pathak; V.K. Singh; Yuktika Gupta; Adil Ali Khan; Sarika Goel (Asian Journal of Medical Research, 2020)
Background: Diffusion Tensor Imaging (DTI) is a new noninvasive dimension of magnetic resonance imaging (MRI) that provides insight into the white matter microstructure. In epilepsy, widespread DTI abnormalities have been reported in multiple studies in medical literature. In mesial temporal lobe sclerosis (MTLS) patients, conventional MRI may show enlargement of ipsilateral temporal horn & reduction in volume of hippocampus in later stages of disease. However, DTI has been found to be useful in demonstrating the focus of epileptiform activity in brain especially in white matter very early in disease. Since DTI is a sensitive technique to detect subtle structural abnormalities causing epilepsy, hence it can be used to plan more successful epilepsy surgery. Therefore, we conducted a pilot study on twenty patients with seizure disorder using DTI where focal organic brain lesions were ruled-out. Aim: To assess the role of DTI in patients of MLTS with seizures.Subjects and Methods:Twenty patients with seizure disorder secondary to MLTS were evaluated using conventional MRI and DTI. We compared the final diagnosis achieved by clinical parameters correlated with EEG localization.Results:Ten out of twenty patients revealed abnormality on DTI that correlated with EEG correlation without obvious abnormality on conventional MRI representing a significant impact of DTI.Conclusion: DTI can sensitively detect structural changes in MLTS with epilepsy often undetectable on conventional MRI. Hence, DTI can serve as an important radiological tool guiding in management and presurgical evaluation of epilepsy patients considered as idiopathic or and refractory medication.